Mechanism of auxin perception by the TIR1 ubiquitin ligase. - Tan, X; Calderon-Villalobos, L; Sharon, M; Zheng, C; Robinson, C; Estelle, M; Zheng, N (2007)
Auxin is a pivotal plant hormone that controls many aspects of plant growth and development. Perceived by a small family of F-box proteins including transport inhibitor response 1 (TIR1), auxin regulates gene expression by promoting SCF ubiquitin-ligase-catalysed degradation of the Aux/IAA transcription repressors, but how the TIR1 F-box protein senses and becomes activated by auxin remains unclear. Here we present the crystal structures of the Arabidopsis TIR1-ASK1 complex, free and in complexes with three different auxin compounds and an Aux/IAA substrate peptide. These structures show that the leucine-rich repeat domain of TIR1 contains an unexpected inositol hexakisphosphate co-factor and recognizes auxin and the Aux/IAA polypeptide substrate through a single surface pocket. Anchored to the base of the TIR1 pocket, auxin binds to a partially promiscuous site, which can also accommodate various auxin analogues. Docked on top of auxin, the Aux/IAA substrate peptide occupies the rest of the TIR1 pocket and completely encloses the hormone-binding site. By filling in a hydrophobic cavity at the protein interface, auxin enhances the TIR1-substrate interactions by acting as a 'molecular glue'. Our results establish the first structural model of a plant hormone receptor.